DETERMINAN GENERASI MILLENIAL TERHADAP MINAT MENGGUNAKAN BSI MOBILE DENGAN GAYA HIDUP SEBAGAI VARIABEL MODERASI - Afif, Nu'man; Afdawaiza, Afdawaiza (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine the effect of the variables of usability, convenience and corporate image on millennial students in using BSI Mobile which focuses on Central Java Province and the Special Region of Yogyakarta. The model used is TAM with the addition of lifestyle as a moderating variable. Respondents in this study totaled 220 BSI Mobile users who were included in the millennial generasi category and were spread across Central Java Province and the Special Region of Yogyakarta. The approach used is descriptive quantitative using SEM (structural equation model) as an analysis model, using SmartPLS 3.0 software. Convenience, usability, corporate image and lifestyle as usability moderating variables have an influence on millennial students in using BSI Mobile. However, lifestyle as a moderation of convenience and lifestyle as a variable for moderating corporate image have no effect on millennial students in using BSI Mobile. The results of these findings are expected to contribute to an understanding of the decision to use BSI Mobile in Indonesia, especially in the context of Mobile Banking services from an academic perspective.